COMIC DEVELOPMENT OF CHILDREN'S STORIES WITH THE THEME OF CLEAN HEALTHY AND BEAUTIFUL ENVIRONMENT FOR READING MATERIALS IN LOWER CLASS - Paula Ariska Wati (Yayasan Thaifah Manshurah Pekanbaru, 2022)
This study aims to produce children's story comics with the theme of a clean, healthy, and beautiful environment for reading materials in lower grades and to determine the feasibility of using children's comics. This development research uses Research and Development research methods with the ADDIE model, namely Analys (analysis), Design (design), Development (development), Implementation (application), Evaluation (evaluation). The development of children's story comics was made using the Clip Studio Paint and Ibis Paint X applications. The comics were validated by design experts, linguists, and field user validators. Based on the results of the feasibility test, the average percentage of results obtained by design experts is 90.63% and linguists 92.7%. Meanwhile, the percentage result by field user validators for comic design was 94.79% and the percentage result for comic language was 93.05%. The results of this development research show that children's story comics with the theme of a clean, healthy, and beautiful environment for reading materials in lower grades are very suitable for use for lower grade students.